2021
DOI: 10.1242/bio.058623
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy facilitates dysplastic and tumorigenic phenotypes in the Drosophila gut

Abstract: Aneuploidy has been strongly linked to cancer development, and published evidence has suggested that aneuploidy can have an oncogenic or a tumor suppressor role depending on the tissue context. Using the Drosophila midgut as a model, we have recently described that adult intestinal stem cells (ISCs), do not activate programmed cell death upon aneuploidy induction, leading to an increase in ISC proliferation rate, and tissue dysplasia.  How aneuploidy impacts ISCs in intestinal tumorigenic models remains to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Studies have shown that aneuploidy in ISCs has contrasting effects, either causing ISC overproliferation to form gut dysplasia ( Resende et al 2018 ; Brás et al 2021 ) or ISC loss due to premature differentiation ( Gogendeau et al 2015 ). Our results were apparently against the notion that aneuploidy increased ISC proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that aneuploidy in ISCs has contrasting effects, either causing ISC overproliferation to form gut dysplasia ( Resende et al 2018 ; Brás et al 2021 ) or ISC loss due to premature differentiation ( Gogendeau et al 2015 ). Our results were apparently against the notion that aneuploidy increased ISC proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…As compared with the other proliferative cells ( Morais da Silva et al 2013 ), studies indicated that adult stem cells might tolerate aneuploidy instead of activating apoptosis ( Mantel et al 2007 ; Harper et al 2010 ). Subsequently, aneuploidy could induce the differentiation of ISCs ( Gogendeau et al 2015 ) or promote their proliferation and gut dysplasia ( Resende et al 2018 ; Brás et al 2021 ) in Drosophila .…”
Section: Introductionmentioning
confidence: 99%
“…Aneuploidy can result in failure to survive, developmental abnormalities, or the initiation and development of diseases such as cancer, depending on its sternness [14][15][16]. Some studies have shown that aneuploidy induced by SAC damage in the midgut of drosophila will lead to abnormal intestinal development or tumorigenesis [17]. The SAC mechanism is used by cells during mitosis to guarantee that all chromosomes have enough time to attach to spindle microtubules before the cell divides [5,18].…”
Section: Discussionmentioning
confidence: 99%